Virginijos Woolf romanas „Džeikobo kambarys“ (Jacob’s room 1922): charakterio kūrimo forma - Bartkuvienė, Linara (Literatūra, 2007)
The present article seeks to discuss the genealogy of the form of the character of Virginia Woolf’s novel “Jacob’s Room”. The arguments presented here suggest that there is an indirect relationship between Woolf’s aesthetic and philosophical principles, as manifested in the novel “Jacob’s Room”, and Bertrand Russell’s theory of knowledge. Since Woolf and Russell were members of Bloomsbury Group, they both shared the same intellectual space of the 20th century England and, among others, contributed to the formation of Bloomsbury aesthetics. The article goes on to suggest that although there is no direct evidence of Woolf integrating Russell’s theory of knowledge into the formation of Jacob’s character or/and the form of the novel’s narrative, it is possible to distinguish several premises that open new reading vistas and help better understand and, therefore, appreciate Woolf’s method of creating character.